PENGARUH UKURAN PERUSAHAAN, RASIO ARUS KAS OPERASI, DAN EFISIENSI INVESTASI TERHADAP FINANCIAL DISTRESS PADA SEKTOR BARANG KONSUMSI NON-SIKLIKAL DI INDONESIA - Nugroho, Felix Cahyo; Kusumadewi, Ni Luh Gde Lydia (Universitas Katolik Indonesia Atma Jaya, 2025)
Financial distress occurs when a company experiences financial difficulties that may result in bankruptcy. Internal challenges within the company are one factor contributing to financial distress. This study examines the influence of firm size, operating cash flow ratio, and investment efficiency on financial distress in noncyclical sector companies listed on the Indonesia Stock Exchange from 2018 to 2023. The research employs multiple linear regression analysis using IBM SPSS version 27. A purposive sampling technique was applied, resulting in 374 observation units. The findings indicate that firm size has no significant impact on financial distress. However, operating cash flow ratio and investment efficiency negatively affect financial distress, suggesting that higher cash flow and efficient investments reduce the likelihood of financial distress